Skills Workers in Mechanical Engineering to Produce Portable Sprocket - Omar Ali Saifuddin bin Wan Ismail, W; binti Hamzah, Noraini; Nazafee bin Mohd Ridhuan Tee, Mohd (International Journal of Engineering and Technology, 2018)
Sprocket is a wheel with teeth that mesh with a chain. It is being used widely in automotive andÂ Â Â Â Â machinery to transmit rotary motion between the shafts. In manufacturing the sprockets, some of the workers have the skills to make it and some of them lack the skills. Skills are important in manufacturing engineering. The main focus of this research is to help: i. the workers in manufacturing the sprocket efficiently; and ii. low cost while providing good quality of sprocket. In this research, operations that require machining some of them are simple which can be done easily such as turning. No other devices needed to hold the workpiece in such an operation. The research aims to develop a jig & fixture tool which is called a sprocket. While the research methodology is divided into 2 which are the procedure during the making of the project and the results and discussion obtained. This study is very useful for small and big industries for the sprocket process. It would help the user to make sprockets only using this sprocket maker to guide the drilling machine. It is a low cost and efficient way for manufacturers that is currently in this sprocket manufacturing.Â Â